The impact of service quality, family support, and coach-athlete intimacy on the achievement performance of student-athletes through motivation as a mediator - Ali Mandan,; Tomoliyus,; Abdul Alim,; Endang Rini Sukamti,; Fauzi,; Awan Hariono,; Trisnar Adi Prabowo, (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed at measuring service quality, family support, coach-athlete intimacy to student-athlete achievement performance through motivation as a mediator. This was a correlational descriptive study that utilized the SEM (Structural Equation Modeling) approach with the assistance of Smart PLS. The researchers developed an instrument based on previous research data with a scale of 1–4. The subjects of this study were 125 Riau province student-athletes who will compete at POPNAS (National Student Sports Week) in Indonesia. Subjects consisted of 73 male athletes and 52 female athletes aged 15 ± 1.6 years. For data analysis, we used Smart PLS. The structural relationship model testing generated ten hypotheses. Among these, only the relationship between Coach-Athlete Intimacy and Achievement Performance showed a p-value of 0.532 > 0.05, indicating a lack of significant effect. However, the remaining nine hypotheses demonstrated a significant effect. The research model fulfills the fit model criteria, with data based on an SRMR (Standardized Root Mean Square) value of 0.064. The publication of this study anticipates improvements in service quality, family support, and nurturing coach-athlete relationships to enhance athlete motivation and achievement performance. Further research endeavors are essential to expand the sample size and explore additional variables influencing sports achievement.